Chasing the monster idea : the marketer's almanac for predicting idea epicness - Mumaw, Stefan (Wiley, 2011)
The latest from the author of the bestselling Caffeine for the Creative Mind How do you develop solutions that rock? Ones that surpass their initial purpose and grab an industry by its throat, turn interested parties into concept evangelists, and influence behaviors and alter perceptions? Read Chasing the Idea Monster and find out. This fun and insightful book sorts out the hallmarks of a monstrous idea by providing the author's "idea measurement" tools in the form of seven primary questions to gauge the potential of any idea. These seven questions are supported by real-world examples of ideas that succeeded in winning over their audience, as well as those that ignored the measurement and failed miserably. Features warnings and anecdotes from some of the world's most prominent creatives, marketing teams, and business professionals A proven method for determining if an idea will be a "big idea," or else will die a painful death Author is a respected industry expert whose Caffeine for the Creative Mind successfully reached an audience both in the creative community and beyond Want to get a better sense of what makes a successful idea, and how yours measures up? Start Chasing the Idea Monster and scoring big creative wins today!